Renaissance of Gold Mining in Egypt - Kh. E. Sharafeldin; A. A. Vercheba (Vestnik Permskogo universiteta. Serii͡a︡ Geologii͡a, 2019)
The article provides information about gold mining in Egypt over a period about 4,000 years of republic history. Despite its rich past, in its current state, Egypt’s gold mining industry is not a leading sector in the country's economy. Interest in Egyptian gold mining is gradually increasing, gained by the success of the gold mining company “Centamin” at the Sukari mine. The reproduction of the mineral resources of gold can be based on the development of the most important gold formations and geological-industrial types of gold deposits. Gold-sulphide-quartz ores in the intrusive bodies of collisional granitoids represent the greatest geological and economic values for the growth of reserves and resources. For this type of deposits, a rational forecasting-exploration complex has been developed for geological prospecting in the Eastern desert of Egypt.